Tubeless Supine Mini-Percutaneous Nephrolithotomy (mini-PCNL) for Renal Stone: 50 Cases Experiences (Bangladesh Journal of Urology, 2025)
Background: To present our experience in performing tubeless supine mini-percutaneous nephrolithotomy and to compare our results with those reported in the international literature.Patients and Methods: The medical records of 50 patients that underwent supine mini-percutaneous nephrolithotomy were reviewed. The evaluated variables were: age, gender, stone location and size, surgery duration, success rate, and complications.Results: The mean age of the patients was 42.28 + 13.06 years (20-60) with predominance of males (30:20). Mean stone size was 1.5+ 0.65 cm (range: 1- 3 cm), predominantly on left side (32:18) and the mean operative time was 40.6 + 4.8 min (range: 30-60 min). Topography of the calculi were pelvic, 24 (48%); caliceal system; lower 12 (24%), middle 11 (22%), upper 3 (6%). The stone clearance rate was 98%, and the complication rate was 6% (Clavien: I).Conclusion: Supine mini-percutaneous nephrolithotomy is safe and efficacious, with a high success rate, low complication rate, and undisputable advantages of anesthesia management.Bangladesh J. Urol. 2024; 27(1): 16-22